Tinjauan Maqashid Syariah dan Fiqh al-Bi’ah dalam Green Economy - Muhtadi, Ridan; Utama, R Wahyu Agung; Arifin, Nur Rachmat; Mawardi, Imron (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Economic development in the 20th century has a huge impact on the sustainability of mankind. However, on the other hand, it has a negative impact on the living ecosystem. Economics and the environment are considered two opposite sides in some ways like the way they treat profit orientation toward sustainable development. Sustainable development On the basis of this result creates a relatively new concept, Green Economy. Green Economy is a concept that supports human welfare and care for the preservation of the environment and ecosystem of life in economic development. But the negative side of economic development could also affect the depletion of natural resources due to overexploitation, pollution of the land, water, and air due to industrial pollution, floods, and impact on climate change. Islam has an ideal concept of sustainable development. There are at least fundamental rules in order to support the sustainable development of the implementation of environmental fiqh based maqasid sharia for the management of Islamic resources in economic transactions.   Keywords: Maqasid Syariah, Fiqh environment, Green Economy, Environmental Preservation